Effect of vinylene carbonate on electrochemical performance and surface chemistry of hard carbon electrodes in lithium ion cells operated at different temperatures. (20th December 2016) - Zhang, Xiang; Fan, Changling; Xiao, Ping'an; Han, Shaochang
Abstract: Due to wide uses of lithium ion batteries and emerging researches on sodium ion batteries, hard carbon (HC) as an anode material comes into sights of research fellows recently. HC anode delivers a considerable reversible capacity at room temperature and increasing capacities at elevated temperatures. However, the electrolyte and solid electrolyte interphase (SEI) formed on the electrode surface tend to become instable at elevated temperatures, though the appreciable reservoir ability of HC is alluring. Herein, we report that vinylene carbonate (VC) is a desirable electrolyte additive for HC electrodes especially at elevated temperatures. The influence of VC on electrochemical performance and surface chemistry of HC electrodes at both 25 °C and 50 °C is investigated in detail using Cyclic voltammograms (CVs), electrochemical impedance spectroscopy (EIS), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). In the presence of VC additive, a stable SEI film is formed upon cycling, which contains increased amounts of Li2 CO3 and decreased F species contents. It demonstrates that the SEI formed in the presence of VC helps suppress salt anion (PF6 − ) decomposition as well as SEI transformation occurred at 50 °C.